ANALISIS MASYARAKAT TERHADAP PELAKSANAAN POSYANDU CEMPAKA PUTIH KELURAHAN TANGKERANG SELATAN KECAMATAN BUKIT RAYA KOTA PEKANBARU - Suryani, Suryani; Bahar, Aswandi; Widiastuti, Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: This study aims to find out information about people's analysis Strengths, Weaknesses, Opportunities and Threats implementation of IHC Cempaka Putih Village South Tangkerang District of Bukit Raya Pekanbaru City. The benefits of this study was 1) Useful to contribute to education in general, 2) besides that is expected to provide benefits to the student and academic community to understand the existence of IHC in the midst of the community, 3) can provide practical benefits for activists or IHC manager for the public interest in the use of IHC in each environment. To obtain these data, the data collection techniques are used Questionnaire. While the source of research data is taken from the primary data is data taken directly from the respondents (population) penelitianya mothers always carry a baby or babies to IHC Cempaka Putih Village South Tangkerang District of Bukit Raya Pekanbaru City and juaga of primary data that includes all information required to compile research data in the form of concepts, definitions or theories that can be used to explain the problems that will be implemented through this research. The results of this study are based on data analysis can be argued that research findings Society Analysis of Implementation IHC Cempaka Putih Village South Tangkerang District of Bukit Raya Pekanbaru City is included in the category of '' good '' seen from the average indicator Strength (weakness), Weakness (weakness ), opportunity (opportunity), and threat (threat) is 70% (SB / SS / SP + B / S / P).Keywords: Community Analysis, Implementation Posyandu, SWOT